Effect of iron chelators on proliferation and iron uptake in hepatoma cells - Kicic, Anthony; Chua, A.C.G.; Baker, E. (JOHN WILEY & SONS INC, 2001)
Background. The siderophore desferrioxamine mesylate (DFO) is used routinely in clinical practice to treat diseases of iron (Fe) overload. Recent studies suggest that DFO and other chelators may have potential in the treatment of cancer. The current study reports the findings obtained when a number of chelators with varying membrane permeability, Fe-binding affinity, and preference for either Fe3+ or Fe2+ were assessed for their antineoplastic potential in vitro against hepatocellular carcinoma cells (HCC) because to the authors' knowledge there are few effective treatment methods for this aggressive neoplasm. Methods. A number of criteria were investigated, including the effects of the chelators on cell proliferation, selectivity, Fe uptake, toxicity, and cell cycle progression. Results. The results obtained showed that Fe binding affinity did appear to influence Fe chelator activity but was not an absolute factor, and that certain ferric and ferrous, membrane-permeable and membrane-impermeable Fe chelators demonstrated antiproliferative activity and selectivity against HCC. All effective chelators inhibited Fe uptake from Tf-59Fe in both hepatoma cells and normal hepatocytes. However, these chelators all had much lower effects on the survival of normal proliferating and nonproliferating cells. The effects on cell cycle were more varied between chelators, as were levels of toxicity. Conclusions. The results of the current study indicate that a number of different Fe chelators have the potential to treat HCC, and that further investigation into their mechanisms of action is warranted. © 2001 American Cancer Society.